Konsumsi Fast Food Mahasiswa dalam Perspektif Masyarakat Risiko: antara Kesadaran dan Praktik: Studi pada Mahasiswa Universitas Sriwijaya - Angga Aji Saputra; Napinurul Azizah; Reza Anada Putri; Vieronica Varbi Sununianti; Istiqomah Istiqomah; Deni Aries Kurniawan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to analyze public concerns regarding fast food consumption from the perspective of risk society, particularly among university students. The increasing consumption of fast food reflects shifts in consumption patterns influenced by globalization, practicality, and time efficiency. This research employs a qualitative approach through a literature review supported by interview data to strengthen the analysis. The findings reveal that fast food consumption is not solely driven by biological needs but also by practical, emotional, and social factors. Although students demonstrate a relatively high awareness of health risks associated with fast food, their consumption behavior persists as an adaptive response to structural conditions such as time constraints, accessibility, and academic pressures. From the perspective of risk society, this phenomenon illustrates a contradiction between risk awareness and everyday consumption practices. Risks produced by modernity are not entirely avoided but are negotiated and normalized in daily life. Therefore, fast food consumption cannot be understood merely as an individual choice but as a result of the interaction between structural factors, consumer culture, and social construction within modern society.